RESILIENCE AND INCLUSION IN AGRICULTURAL EXTENSION FOR FOOD SECURITY IN THE DIGITAL ERA - Nurhikmah, Nurhikmah (MAP Observer: Jurnal Penelitian Administrasi Publik, 2025)
The rapid climate change, population growth, and global economic instability have put the agricultural sector at a crucial juncture. These challenges necessitate agricultural extension to focus not only on technical knowledge transfer but also on strengthening human resource capacity to cope with stress and adapt to changes. Resilience and inclusion are key components in addressing these challenges. Resilience enables farmers and agricultural leaders to withstand pressures, while inclusion ensures that all community members, including vulnerable groups, can participate and benefit from innovations. The digital era offers technologies that can significantly enhance agricultural productivity and efficiency. However, adopting these technologies requires high resilience and adaptability among farmers and agricultural leaders. This article aims to analyze the role of resilience and inclusion in agricultural extension and how it can enhance food security in the digital age. Keywords: Resilience, Inclusion, Agricultural Extension, Food Security, Digital Era